Improving the acousto-optic detection of high-intensity focused ultrasound lesions - Adams, M; Wang, Q; Cleveland, R; Roy, R (2013)
Real-time acousto-optic (AO) sensing has been shown to non-invasively detect changes in ex vivo tissue optical properties during high-intensity focused ultrasound (HIFU) exposures. Although proof-of-concept experiments have been successful, the underlying parameters and mechanisms affecting the AO detectability of HIFU lesion formation are not well understood. In this work, a modeling based approach is used to improve the AO sensing of lesion formation during HIFU therapy. The angular spectrum method is used to model the acoustic field from the HIFU source and the temperature field, due to the absorption of ultrasound, is modeled using a finite-difference time-domain solution to the Pennes bioheat equation. Wavelength specific changes in tissue optical properties are calculated using a thermal dose model, calibrated by experimental data. The diffuse optical field is modeled using an open-source graphics processing unit accelerated Monte Carlo algorithm The Monte Carlo algorithm is modified to account for light-sound interactions, using the acoustic field from the angular spectrum method, and to account for AO signal detection. Results will demonstrate the important roles of optical wavelength selection, and illumination and detection configurations on the detectability of HIFU lesions by optical and AO sensing methods. © 2013 Acoustical Society of America.